2019
DOI: 10.1136/bmjopen-2018-024980
|View full text |Cite
|
Sign up to set email alerts
|

Occasional and persistent frequent attenders and sickness absences in occupational health primary care: a longitudinal study in Finland

Abstract: ObjectivesFrequent attenders (FAs) create a substantial portion of primary care workload but little is known about FAs’ sickness absences. The aim of the study is to investigate how occasional and persistent frequent attendance is associated with sickness absences among the working population in occupational health (OH) primary care.Setting and participantsThis is a longitudinal study using medical record data (2014–2016) from an OH care provider in Finland. In total, 59 676 patients were included and categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…There were differences between the age groups in how well different measures, i.e., OHS patterns, predicted SA. In line with previous studies [6,7], we showed that the employees with a risk of subsequent SA might be identified by their frequent OHS utilization. The present study further showed that frequent attendance may be captured by different utilization pattern categories: the traditional frequent attendance measure as the cumulative visits within a year, but also by the clustered patterns of OHS visits.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There were differences between the age groups in how well different measures, i.e., OHS patterns, predicted SA. In line with previous studies [6,7], we showed that the employees with a risk of subsequent SA might be identified by their frequent OHS utilization. The present study further showed that frequent attendance may be captured by different utilization pattern categories: the traditional frequent attendance measure as the cumulative visits within a year, but also by the clustered patterns of OHS visits.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, OHS is one potential site for promoting effective workplace interventions for preventing SA due to mental disorders. The utilization of health care services is a known contributor to inequalities in health [4,5], and previous study from Finland found that frequent attendance at OHS is associated with subsequent SA [6], which in turn may lead to disability pension [7][8][9]. A gap in knowledge remains about the role of OHS utilization in the processes leading to health inequalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our linked study on frequent attenders in occupational health services similarly identified women as at risk of frequent use of services [23], where particularly women from the service industry and public administration were at risk [23]. We also found that frequent attenders of OHS primary care are also at increased risk of sickness absences after their consultation frequency has diminished [24]. This supports the lack of impact on sickness absences, when no workplace intervention was included.…”
Section: Discussionsupporting
confidence: 67%
“…Our linked study on frequent attenders in occupational health services similarly identified women as at risk of frequent use of services more than men (22), a risk that was higher for women from the service industry and public administration (22). We also found that frequent attenders of OHS primary care are at an increased risk of sickness absences also after their consultation frequency has diminished (23). This supports the the lack of impact on sickness absences, when no workplace intervention was included.…”
Section: Discussionsupporting
confidence: 66%